Getting the point: Tracing worked examples enhances learning. (February 2015) - Hu, Fang-Tzu; Ginns, Paul; Bobis, Janette
Abstract: Embodied cognition and evolutionary educational psychology perspectives suggest pointing and tracing gestures may enhance learning. Across two experiments, we examine whether explicit instructions to trace out elements of geometry worked examples with the index finger enhance learning processes and outcomes. In Experiment 1, the tracing group solved more test questions than the non-tracing group, solved them more quickly, made fewer errors, and reported lower levels of test difficulty. Experiment 2 replicated and extended the findings of Experiment 1, providing evidence for a performance gradient across conditions, such that students who traced on the paper outperformed those who traced above the paper, who in turn outperformed those who simply studied by reading. These results are consistent with the activation of an increasing number of working memory channels (visual, kinaesthetic and tactile) for learning-related processing. Highlights: Pointing and tracing with an index finger may enhance communication and learning. Two experiments tested tracing effects on learning from worked examples. Tracing enhanced test scores and cognitive load during test phase. Tracing reduced errors and solution times across test questions.